Effect of Financial Risk, Capital Structure, Banking Liquidity on Profitability of Nepalese Commercial Banks - Magar, Bikash Thapa; G.C., Bishal; Shah, Brij Bihari; Pant, Dikshya; Pradhan, Radhe Shyam (Nepalese Journal of Finance, 2025)
This study examines the effect of financial risk, capital structure, banking liquidity on profitability of Nepalese commercial banks. Return on assets and return on equity are the selected dependent variables. The selected independent variables are non-performing loans, loan loss provision, capital adequacy ratio, debt-to-equity ratio, loan-to-deposit ratio and liquidity ratio. The study is based on secondary data of 10 Nepalese commercial banks with 100 observations for the study period from 2014/15 to 2023/24. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of financial risk, capital structure, banking liquidity on profitability of Nepalese commercial banks. The study showed that non-performing loan has a negative impact on return on assets and return on equity. It indicates that increase in non-performing loan leads to decrease in return on assets and return on equity. Similarly, loan loss provision has a negative impact on return on assets and return on equity. It indicates that increase in loan loss provision leads to decrease in return on assets and return on equity. However, capital adequacy ratio has a positive impact on return on assets and return on equity. It indicates that increase in capital adequacy ratio leads to increase in return on assets and return on equity. In contrast, debt-to-equity ratio has a positive impact on return on assets and return on equity. It indicates that increase in debt-to-equity ratio leads to increase in return on assets and return on equity. Likewise, loan-to-deposit ratio has a positive impact on return on assets and return on equity. It indicates that higher the loan-to-deposit ratio, higher would be the return on assets and return on equity. However, liquidity ratio has a negative impact on return on assets and return on equity. It indicates that increase in Liquidity ratio leads to decrease in return on assets and return on equity.